The Development of Teaching Materials Based on Local Wisdom Society Preventing The Radicalism in West Kalimantan - Budiyono Budiyono (AT-TURATS, 2020)
This research aims to encounter radicalism that is a problem of learning Islam in education institutions in Indonesia through the preparation of local wisdom-based teaching materials in West Kalimantan. The Center for Islamic and Community Studies (PPIM) UIN Jakarta conducted a research on "the exclusive understanding of Islamic education" in 2016 came to the conclusion that the understanding of religious intolerance is still being found through the presentation of teaching books in schools that underscored the dialogical aspects and tend to prioritize one particular view. This research used qualitative methods with the type of literature research. Data collection techniques with documentation, identifying discourse from books, papers or articles, magazines, journals, newspapers, websites (Internet) and other sources related to the study of the teaching materials development in particular in Madrasah Tsanawiyah based local wisdom in West Kalimantan. The theoretical approach used in teaching materials development, through the Minister of Religious Regulation No. 183 year 2019 about the Islamic Lesson(PAI) curriculum and Arabic language at Madrasah. Development of teaching materials based on West Kalimantan Society local wisdom prioritizes religious behaviour that takes place with cultural approaches. Researchers identified and synthesis a variety of research outcomes on cultural-based religious activities. Most cultural-based religious activities have a evidence as mentioned in the Qur'an and Hadith Rasulullah SAW, with a dialogical approach in the preparation of teaching materials to be delivered to students are expected to minimize the thought tends to be stiff